Penyuluhan Kesehatan dan Senam Hipertensi pada Lansia di Desa Solea Kabupaten Seram Bagian Barat - Zasendy Rehena; Andriana Ritje Nendissa (LLDikti Wilayah XII Maluku dan Maluku Utara, 2021)
The KKN-PPM activity in Solea Village, West Seram Regency was carried out based on the problems of the partner group that hypertension in Solea was included in the list of 10 non-communicable diseases that mostly suffered by the elderly. Based on the team's interviews with health workers in Solea village, information was obtained that most of the elderly did not understand how to prevent, recognize and treat hypertension symptoms, as well as the lack of participation of the elderly in elderly posyandu activities so that it had an impact on their health. The aim of the KKN-PPM is to improve the health and knowledge of the elderly about hypertension, and efforts to overcome it through counseling activities, blood pressure checks and hypertension exercises. The methods used are as follows: 1) Counseling about hypertension, its causes, symptoms, and efforts to overcome it, 2) Examination of blood pressure in the elderly, 3) Implementation of hypertension exercise. The results of this activity were: 1) The knowledge of the elderly increased after counseling activities, 2) The first examination showed that there were 10 people (41.7%) of normal elderly blood pressure (41.7%), 8 people (33.3%) prehypertension, stage- hypertension. 1 totaled 5 people (20.8%), and stage-2 hypertension only 1 person (4.2%), 3) Anti-hypertensive exercise which was done 2 times in 2 weeks showed a change in blood pressure in the elderly, from hypertension to normal. Keywords: Health Education, Hypertension Gymnastics, Elderly